2013
DOI: 10.11609/jott.o3857.5214-27
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position and osteology of Pethia setnai (Chhapgar & Sane, 1992), an endemic barb (Teleostei: Cyprinidae) of the Western Ghats, India, with notes on its distribution and threats

Abstract: Abstract:Pethia setnai is an endemic and threatened freshwater fish of the Western Ghats of India. It has a restricted distribution in the west flowing rivers in the states of Maharashtra, Goa and Karnataka. We clarify the phylogenetic position of Pethia setnai, provide osteological details of topotypic material, and morphometric data of specimens from Maharashtra, Goa and Karnataka. We also provide details on micro-level distribution, habitat and threats to the species in its native range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Gills were harvested from two fresh specimens (BNHS FWF 100 and WILD-14-PIS-075) and were preserved in absolute Ethanol. DNA extraction, PCR amplification for cytochrome b (cytb) gene sequences and sequencing protocols follow Katwate et al (2013). Sequences were analyzed by BLAST tool (Altschul et al 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gills were harvested from two fresh specimens (BNHS FWF 100 and WILD-14-PIS-075) and were preserved in absolute Ethanol. DNA extraction, PCR amplification for cytochrome b (cytb) gene sequences and sequencing protocols follow Katwate et al (2013). Sequences were analyzed by BLAST tool (Altschul et al 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Sequences generated as part of the study are deposited in GenBank under the accession numbers KJ681101 and KJ681102. For phylogenetic analysis, we used the cytb gene sequences from Katwate et al (2013). GenBank accession numbers for sequences used for comparison are mentioned in the respective figure and in Appendix A. Gene sequences were aligned using MUSCLE (Edgar 2004) and a molecular phylogenetic analysis was performed using the freeware MEGA 6 (Tamura et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…(Mercy & Jacob 2007), Pethia punctata (Day 1865), Pethia setnai (Chhapgar & Sane 1992), Pethia sharmai (Menon & Rema Devi 1993) and Pethia striata Atkore, Knight, Rema Devi & Krishnaswamy 2015. Pethia sanjaymoluri differs from P. lutea, P. narayani, P. punctata, P. setnai and P. striata by having an incomplete lateral line (v. complete) (Day, 1865;Hora, 1937;Chhapgar 2040 , 1992;Menon & Rema Devi, 1993;Katwate et al, 2013Katwate et al, , 2014aAtkore et al, 2015). From its remaining Western Ghats endemic congeners, with incomplete lateral line, P. sanjaymoluri differs based on characteristics listed in Table II.…”
Section: Phylogenetic Positionmentioning
confidence: 99%
“…In India, the genus is represented by 26 species, of which nine are endemic to the southern region of the peninsula. With the description of several new species, clarifications on the identity of species described in the 19th century and delimitation of species distributional ranges (Knight et al , ; Dishma & Vishwanath, ; Katwate et al , 2013, 2014 a , b , c , 2015; Knight, ; Lalramliana et al , ; Atkore et al , ; Batuwita et al , ), the genus has recently been of interest to fish taxonomists. It has been suggested that there could be several more undescribed species within this genus, especially in the northern part of the Western Ghats, from where relatively few studies are available (Dahanukar et al , ; Katwate et al , 2014 b , c ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation